Imaging Blood Vessel Morphology in Skin: Dynamic Optical Coherence Tomography as a Novel Potential Diagnostic Tool in Dermatology - Schuh, Sandra (Dermatol Ther (Heidelb), 2017)
Conventional optical coherence tomography (OCT) enables the visualization of morphological changes of skin cancer. The use of OCT in the diagnostic investigation and in the therapy decision of non-melanoma skin cancer and other skin changes is already established, and has found its way into routine practice. With the development of speckle-variance OCT, also named dynamic OCT (D-OCT), the vascular architecture and the blood flow of the skin can be displayed in vivo and in 3D. This novel angiographic variant of OCT offers the ability to visualize and measure vessel morphology providing a new insight into healthy, inflammatory and neoplastic skin lesions such as malignant melanoma. This review focuses on the possibilities of using D-OCT on healthy and diseased skin. We suggest and illustrate key diagnostic characteristics by analyzing the initial publications and preliminary unpublished data on vessel morphology and distribution. The potential of D-OCT as a diagnostic tool in dermatology is examined and may give rise to future studies on D-OCT, which are needed to confirm the aforementioned features.